ÇOK AŞAMALI PROSESLERDE ÖRNEK HACMİNİN BELİRLENMESİ ÜZERİNE BİR MODEL VE GENETİK ALGORİTMALAR YARDIMIYLA ÇÖZÜM ÖNERİSİ. - Kaya, İhsan (Selcuk University Social Sciences Institute / Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2006)
In this study, genetic algorithms (GAs) approach was investigated for problems of acceptance sampling in multistage processes. A computer program which was coded Visual Basic Computer Programming Language 6.0 was prepared to solve of multistage inspection problems help of a model which was improved by Langner (2001) and results of this model which was solved by GAs were compared results of ANSI/ASQC Z1.4 Acceptance Sampling Standards. Operating Characteristics (OC) and Acceptance Probability (Pa) diagrams were created depend on sampling number, n, and acceptance number, c, help of WinQSB program and theirs results were analyzed.